Prevalence and molecular characterization of metallo-β-lactamases in Pseudomonas aeruginosa in Palestine - Shtayah, Amani (An-Najah National University, 2016)
Fifty-one clinical isolates of Pseudomonas aeruginosa were obtained from different hospitals and private labs in the West Bank-Palestine, during October 2015- April 2016. Isolates were confirmed in microbiology laboratory at An-Najah National University, Nablus-Palestine. The prevalence of extended spectrum beta-lactamases, metallo-beta-lactamases and integrons was studied by conventional and/or molecular methods. Results showed that 21.6% of P. aeruginosa isolates were ESBL producers using conventional methods. The prevalence of metallo-β-lactamases using conventional and molecular methods was 60.8% and 29.4% respectively. The most dominant MBL gene among MBL-producing P. aeruginosa isolates was VIM gene (60%), while the prevalence of IMP and SPM+VIM was 33.3% and 6.7% respectively. Neither GIM nor SIM were detected. The results also showed that 23.5% of P. aeruginosa isolates carried class I integrons. Neither class 2 nor class 3 integrons were detected. All isolates harboring MBL genes detected by PCR (15) were analyzed by ERIC-PCR. ERIC-PCR profile, of P. aeruginosa isolates harboring MBL genes (15), showed 4 clones circulating among the hospitals from which isolates were collected. The present study showed high prevalence of MBLs and ESBLs among clinical isolates of P. aeruginosa in the West Bank-Palestine. Based on these results, continuous monitoring and surveillance of the prevalence, proper prevention practices and use of effective antibiotics to limit and restrict the further spread of ESBLs and MBLs producing pathogens including P. aeruginosa within and among hospitals in Palestine.
الوصف الجزيئي ومدى انتشار الزائفة الزنجارية المنتجة لانزيمات البيتا-لاكتاميزيز الفلزية في نابلس-فلسطين